Brain gut microbiota axis. Importance in clinical practice - Bustos-Fernández, Luis María (2022)
The brain-gut-microbiota axis is a bidirectional complex that connects the central nervous system with the digestive system. Alterations in the composition of the intestinal microbiota have been linked to the presence of digestive and extradigestive diseases such as neuropsychiatric diseases. Dysbiosis predisposes to the appearance of alterations in intestinal permeability, which facilitates the release of neurotransmitters and cytokines that generate favorable conditions for the appearance of a state known as neuroinflammation, which seems to be key in the physiopathogenesis of neuropsychiatric diseases. Based on these data, the modulation of the microbiota through changes in diet, antibiotics and probiotics could be a useful alternative, not only for the treatment of digestive diseases but also extra-digestive disorders such as neuropsychiatric diseases.